Case Reports: Novel Missense Variants in the Filamin C Actin Binding Domain Cause Variable Phenotypes - Velardo, Daniele; D'Angelo, Maria Grazia; Citterio, Andrea; Panzeri, Elena; Napoli, Laura; Cinnante, Claudia; Moggio, Maurizio; Comi, Giacomo Pietro; Ronchi, Dario; Bassi, Maria Teresa (Frontiers in Neurology, 2022)
Filamin C is a large dimeric actin-binding protein, most prevalent in skeletal and cardiac muscle Z-discs, where it participates in sarcomere mechanical stabilization and intracellular signaling, interacting with numerous binding partners. Dominant heterozygous mutations of Filamin C gene cause several forms of myopathy and structural or arrhythmogenic cardiomyopathy. In this report we describe clinical and molecular findings of two Italian patients, in whom we identified two novel missense variants located within the Filamin C actin binding domain. Muscle imaging, histological and ultrastructural findings are also reported. Our results underline the extreme inter- and intrafamilial variability of clinical manifestations, hence the need to extend the investigation also to asymptomatic relatives, and the relevance of a broad diagnostic approach involving muscle electron microscopy, skeletal muscle magnetic resonance imaging and next generation sequencing techniques.